FAKTOR PSIKOLOGIS INVESTOR MILLENIAL DALAM PENGAMBILAN KEPUTUSAN INVESTASI SAHAM (Studi Empiris Pada Investor Millenial di Kota Ambon) - Audry Leiwakabessy; Meidylisa Patty; Baretha M Titioka (ITB AAS INDONESIA, 2022)
Behavioral finance is an approach that explains how humans invest or relate to finances influenced by psychological factors. Behavioral financial theory states that an investor is not always rational in making investment decisions and tends to use psychological aspects. The purpose of this research is to examine the effect of overconfident and herding behaviour to investment decisions of millennial in Ambon city. The population in this study are millennial investors in the city of Ambon and the sample used is 96 respondents. The sampling technique used purposive random sampling, the data in this study used primary data in the form of a questionnaire. The data analysis technique is multiple regression analysis. The results of the study show that overconfidence and herding behavior have a positive and significant effect on the stock investment decisions of millennial investors in Ambon city. The coefficient of determination test shows the Adjusted R2 value of 0.159 or 15.9%, which means that the stock investment decision variable is influenced by overconfidence and herding behavior variables and the remaining 84.1% is influenced by other variables.